Irène - Lemaître, Pierre, 1951- (MaLehose Press, 2014)
For Commandant Verhoeven life is beautiful: he's happily married, and expecting his first child with the lovely Irene. But his blissful existence is punctured by a murder so savage that even the most hardened officers on the force are shaken to the core. In the face of the seemingly motiveless horror, only Verhoeven makes the vital connection - the crime scene resembles one described in a James Ellroy novel too closely for there to be any coincidence. As the stylized murders continue, Verhoeven traces the crimes' literary inspirations, and risks his superiors' ire by taking out adverts to inform the killer of his progress. Before long, the case develops into a personal duel, with each man hell-bent on outsmarting his opponent. There can only be one winner - whoever has the least to lose ...